Economic Development and Growth in Central and Eastern Europe - Csilla Polster (Comparative Economic Research. Central and Eastern Europe, 2021)
The study investigates the economic growth in Central and Eastern Europe in the last 25 years. The economy can be regarded as a substantial topic in any country, but it is even more interesting in developing countries. One of the basic ideas of the European Union is the convergence between member states, namely the reduction of development disparities, which can be achieved through faster economic growth in less-developed countries. Growth theory is one of the main topics in economics. Its significant importance is because the desire for development is one of the main driving forces of mankind. The aim of the study is to reveal the crucial differences and common features between the growth paths of the eleven Central and Eastern European member states of the European Union. After presenting growth theories, the growth performance of the examined Central and Eastern European member states is pinpointed. During the research, GDP per capita, population, migration, activity rate, employment rate, unemployment rate, foreign direct investment and foreign trade openness are considered.
Keywords: E10; 330; economic indicators; labour market processes; economic growth